1977
DOI: 10.1063/1.323728
|View full text |Cite
|
Sign up to set email alerts
|

Pb valence in iron garnets

Abstract: A model for the incorporation of Pb in garnets is presented in which self-compensation occurs via the formation of Pb2+ and Pb4+ and allows an explanation of the following observations: high levels of Pb substitution achievable, the temperature dependence of Pb incorporation, lattice mismatch behavior of epitaxial films of Pb-doped iron garnets, the Pb-induced uniaxial anisotropy behavior in EuIG : Pb, the electrical conductivity type, and the high Pb-induced optical absorption. Spectroscopic evidence for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(36 citation statements)
references
References 22 publications
0
36
0
Order By: Relevance
“…Pb 2+ ions. In [25], it was concluded that in this case the charge and volume of a Pb 2+ ion in the garnet lattice are both compensated by a much smaller Pt 4+ ion located in the Al 3+ site, and, hence, no other defects would be necessary to compensate the Pb 2+ , this being provided by the Pt 4+ . However, recent ESR studies [26] have shown that trivalent Pt 3+ ions are incorporated into the garnet lattice at a concentration of about several hundreds ppm which is comparable with the total Pt content in the SCF studied.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Pb 2+ ions. In [25], it was concluded that in this case the charge and volume of a Pb 2+ ion in the garnet lattice are both compensated by a much smaller Pt 4+ ion located in the Al 3+ site, and, hence, no other defects would be necessary to compensate the Pb 2+ , this being provided by the Pt 4+ . However, recent ESR studies [26] have shown that trivalent Pt 3+ ions are incorporated into the garnet lattice at a concentration of about several hundreds ppm which is comparable with the total Pt content in the SCF studied.…”
Section: Discussionmentioning
confidence: 94%
“…Pb 2+ -based centers of the type of {Pb 2+ -Pb 4+ } In the SCF of garnets with a very large lead content, Pb 4+ ions can also exist [25]. The Pb 2+ and Pb 4+ ions can be localized in dodecahedral positions of the garnet lattice, and in this case they have ionic radii 1.29 Å and 0.94 Å, respectively [24].…”
Section: Singlementioning
confidence: 99%
See 1 more Smart Citation
“…2) consist: (i) the band peaked at 7.95 eV related to the onset of YAG interband transition (Zorenko et al, 2007a); (ii) the dominant bands peaked in 6.67-6.885 eV range, corresponding to the formation of exciton bound with the Ce 3þ ions; (iii) the band peaked at 5.67 eV, related to 4f-5d( 3 T 2g ) transition of Ce 3þ ions; (iv) the band peaked 4.74 eV, caused by the 1 S 0 / 3 P 1 transition of Pb 2þ flux dopant in the SCF (Scott and Page, 1977). Due to Y Al AD presence and formation of Ce-AD coupled centers, the excitation spectra of Ce 3þ luminescence in YAG:Ce SC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the result of ADs elimination, the YAG:Ce and LuAG:Ce SCF phosphors show considerably better timing characteristics under excitation in the range of interband transition with respect to their bulk SC analogues [11,12]. At the same time, at the preparation of SCF by LPE method usually from PbO-based fluxes, lead ions are also introduced into the garnet lattice [16,17] and can influenced on the luminescent and scintillation properties of rare-earth doped SCF phosphors. Namely, the influence of Pb-related centers on the luminescence of Ce 3+ and Pr 3+ ions in YAG and LuAG SCF, grown from PbO-based flux, were investigated in details in our previous works [17][18][19][20].…”
mentioning
confidence: 99%